First Comparative Study of the Effectiveness of the Use of Tranexamic Acid against ε-Aminocapróic Acid via the Oral Route for the Reduction of Postoperative Bleeding in TKA: A Clinical Trial - Morales-Avalos, Rodolfo; Ramos-Morales, Tomas; Espinoza-Galindo, Ana María; Garay-Mendoza, Domingo; Peña-Martínez, Víctor M.; Marfil-Rivera, Luis Javier; Garza-Ocañas, Lourdes; Acosta-Olivo, Carlos; Cerda-Barbosa, Jessica K.; Valdés-González, Nancy L.; Vílchez-Cavazos, Félix (The Journal of Knee Surgery, 2019)
Total primary knee replacement results in significant postoperative bleeding. There are reports that 20 to 50% of the patients require a blood transfusion, which has been related to many complications, resulting in the search for strategies to reduce bleeding. The use of oral antifibrinolytics is becoming a low cost and safe way of achieving this goal. The hypothesis of this study was that the use of oral aminocaproic acid could provide similar results to the use of oral tranexamic acid (TXA). The purpose was to compare the effects of oral aminocaproic acid as a hemostatic agent versus the use of oral TXA administered in multiple doses pre and postsurgery in patients undergoing total primary knee replacement. We enrolled 92 patients that were randomly divided into two groups: received three doses of aminocaproic acid (2,000 mg per dose) or three doses of oral TXA (1,300 mg per dose). The drugs were administered according to the following schedule: 2 hours before surgery and 6 and 12 hours after surgery. The variables that were analyzed to compare the effectiveness of the hemostatic agents were total blood loss; hidden blood loss; external blood loss; transfusion rate; intraoperative blood loss; decreases in hemoglobin and hematocrit values; surgical drainage output; visual analogue scale; and surgical complications. There were no significant differences between any of the study variables for the group receiving oral aminocaproic acid and the group receiving oral TXA (p > 0.05), with the exception of patients who received TXA, who presented with more adverse events (p = 0.04). Our study showed that the use of oral aminocaproic acid was similar to its counterpart TXA regarding the evaluated parameters. Although patients who received TXA presented an average of 140 mL less blood loss than patients in the ε-ACA group, the difference did not appear to be clinically important, the transfusion rate was very low, and there were no between-group differences in postoperative complications.
Keywords: total knee replacement; tranexamic acid; orally; aminocaproic acid; blood loss